2014
DOI: 10.4111/kju.2014.55.6.395
|View full text |Cite
|
Sign up to set email alerts
|

Does the Time From Biopsy to Radical Prostatectomy Affect Gleason Score Upgrading in Patients With Clinical T1c Prostate Cancer?

Abstract: PurposeIt is debated whether treatment delay worsens oncologic results in localized prostate cancer (PCa). Few studies have focused on the role of a delay between the time of biopsy and the time of surgery. Thus, we aimed to investigate the effect of the time period between biopsy and surgery on Gleason score upgrading (GSU).Materials and MethodsA total of 290 patients who underwent radical retropubic prostatectomy in Ankara Training and Research Hospital were included in the study. The biopsy Gleason score, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…This is consistent with previous findings 7, 23. Furthermore, we have shown that a delay of > 9 months or even 6 months not only predicted upgrading, but was also associated with greater biochemical recurrence and positive surgical margins, 26 suggesting that a delay may compromise patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous findings 7, 23. Furthermore, we have shown that a delay of > 9 months or even 6 months not only predicted upgrading, but was also associated with greater biochemical recurrence and positive surgical margins, 26 suggesting that a delay may compromise patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Predictors from the literature include low prostate volume/weight, 3 higher PSA level,5, 22, 23 higher PSA density, 24 older age, 5 clinical stage T2, 25 time interval between diagnosis to RP,7, 23 percentage positive biopsy cores,7, 22 Cancer of the Prostate Risk Assessment (CAPRA) score, 22 higher body mass index,22, 24 and low serum testosterone 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Factors such as PSA, PSA density, prostate volume, BMI, CAPRA score, positive core percentage, low serum testosterone level, and prolonged time intervals between biopsy and surgery were found to be correlated with upgrades. [11][12][13][14][15][16] In our study, most of these factors were found to be effective in the univariate analysis but insignificant in the multivariate analysis. The reasoning behind this could be the fact that we used the new grading system.…”
Section: Discussionmentioning
confidence: 42%
“…17,18 A number of clinicopathologic parameters are associated with Gleason upgrading in RP. [19][20][21][22][23][24][25] However, only 1 study has briefly mentioned the effect of the quantity of GP 4 in needle biopsy on Gleason upgrading, without presenting detailed data. 26 Targeted biopsy using multiparametric magnetic resonance imaging (MRI)-ultrasound fusion techniques has been increasingly used recently in the diagnosis and characterization of PCa.…”
mentioning
confidence: 99%